Maternal and perinatal outcomes during the COVID-19 epidemic in pregnancies complicated by gestational diabetes - Munda, Ana (Zdravstveno varstvo, 2023)
Introduction: Gestational diabetes (GDM) is one of the most common complications in pregnancy, with a prevalence that continues to rise. At the time of the COVID-19 epidemic, immediate reorganisation and adjustment of the system was needed. Telemedicine support was offered in order to provide high-quality treatment to pregnant women. However, the success of the treatment is unknown. We therefore aimed to evaluate COVID-19 epidemic effects on pregnancy outcomes in GDM. Methods: The maternal outcomes (insulin treatment, gestational weight gain, caesarean section, hypertensive disorders) and perinatal outcomes (rates of large and small for gestational age, preterm birth and a composite child outcome) of women visiting a university hospital diabetes clinic from March to December 2020 were compared with those treated in the same period in 2019. Results: Women diagnosed with GDM during the COVID-19 epidemic (n=417), were diagnosed earlier (23.9 11.7–26.0 vs. 25.1 21.8–26.7 gestational week), had higher fasting glucose (5.2 5.0–5.4 vs. 5.1 4.8–5.3 mmol/l) and earlier pharmacological therapy initiation, and had achieved lower HbA1c by the end of followup (5.1% (32.2 mmol/mol) 4.9% (30.1 mmol/mol)–5.4% (35.0 mmol/mol) vs. 5.2% (33.3 mmol/mol) 5.0% (31.1 mmol/mol) – 5.4%·(35.5 mmol/mol), p<0.001) compared to a year before (n=430). No significant differences in perinatal outcomes were found. Conclusions: Although GDM was diagnosed at an earlier gestational age and higher fasting glucose concentration was present at the time of diagnosis, the COVID-19 epidemic did not result in worse glucose control during pregnancy or worse pregnancy outcomes in Slovenia.
Keywords: COVID-19; early screening; gestational diabetes; LGA; nosečnostna sladkorna bolezen; perinatal outcomes; porodni zapleti; telemedicina; telemedicine; zgodnje presejanje